Ischemic Stroke Increases Heart Vulnerability to Ischemia-Reperfusion and Alters Myocardial Cardioprotective Pathways - Meloux, Alexandre; Rigal, Eve; Rochette, Luc; Cottin, Yves; Bejot, Yannick; Vergely, Catherine (Stroke (1970), 2018)
BACKGROUND AND PURPOSE—For years, the relationship between cardiac and neurological ischemic events has been limited to overlapping pathophysiological mechanisms and common risk factors. However, acute stroke may induce dramatic changes in cardiovascular function. The aim of this study was to evaluate how prior cerebrovascular lesions affect myocardial function and signaling in vivo and ex vivo and how they influence cardiac vulnerability to ischemia-reperfusion injury. METHODS—Cerebral embolization was performed in adult Wistar male rats through the injection of microspheres into the left or right internal carotid artery. Stroke lesions were evaluated by microsphere counting, tissue staining, and assessment of neurological deficit 2 hours, 24 hours, and 7 days after surgery. Cardiac function was evaluated in vivo by echocardiography and ex vivo in isolated perfused hearts. Heart vulnerability to ischemia-reperfusion injury was investigated ex vivo at different times post-embolization and with varying degrees of myocardial ischemia. Left ventricles (LVs) were analyzed with Western blotting and quantitative real-time polymerase chain reaction. RESULTS—Our stroke model produced large cerebral infarcts with severe neurological deficit. Cardiac contractile dysfunction was observed with an early but persistent reduction of LV fractional shortening in vivo and of LV developed pressure ex vivo. Moreover, after 20 or 30 minutes of global cardiac ischemia, recovery of contractile function was poorer with impaired LV developed pressure and relaxation during reperfusion in both stroke groups. Following stroke, circulating levels of catecholamines and GDF15 (growth differentiation factor 15) increased. Cerebral embolization altered nitro-oxidative stress signaling and impaired the myocardial expression of ADRB1 (adrenoceptor β1) and cardioprotective Survivor Activating Factor Enhancement signaling pathways. CONCLUSIONS—Our findings indicate that stroke not only impairs cardiac contractility but also worsens myocardial vulnerability to ischemia. The underlying molecular mechanisms of stroke-induced myocardial alterations after cerebral embolization remain to be established, insofar as they may involve the sympathetic nervous system and nitro-oxidative stress.